Machine Learning-Based Phishing Detection: Improving Accuracy and Adaptability - Akhil Mittal (International Journal of Intelligent Systems and Applications in Engineering, 2024)
In this modern era, phishing has become a great problem. Because of this, it can be observed that the personal information of people are leaked from emails & websites. Hence, it is needed that these instances of phishing are to be reduced. In doing one of the best tools that can be used is Machine Learning. This is a process of using historical data for making prediction of future scenarios. In this project, the details of the approached that can be used for the detection of phishing are analyzed. Moreover, the algorithms that are used by ML for this purpose are also envisaged here. The description of the process of collection of data is presented here. In addition to this, the results that shows the effectiveness of ML in the detection of phishing is also discussed here.